The effect of flywheel complex training with eccentric-overload on muscular adaptation in elite female volleyball players - Jiaoqin Wang; Qiang Zhang; Wenhui Chen; Honghao Fu; Ming Zhang; Yongzhao Fan (PeerJ, 2024)
This study aimed to compare the effects of 8 weeks (24 sessions) between flywheel complex training with eccentric overload and traditional complex training of well-trained volleyball players on muscle adaptation, including hypertrophy, strength, and power variables. Fourteen athletes were recruited and randomly divided into the flywheel complex training with an eccentric-overload group (FCTEO, n = 7) and the control group (the traditional complex training group, TCT, n = 7). Participants performed half-squats using a flywheel device or Smith machine and drop jumps, with three sets of eight repetitions and three sets of 12 repetitions, respectively. The variables assessed included the muscle thickness at the proximal, mid, and distal sections of the quadriceps femoris, maximal half-squats strength (1RM-SS), squat jump (SJ), countermovement jump (CMJ), and three-step approach jump (AJ). In addition, a two-way repeated ANOVA analysis was used to find differences between the two groups and between the two testing times (pre-test vs. post-test). The indicators of the FCTEO group showed a significantly better improvement (p < 0.05) in CMJ (height: ES = 0.648, peak power: ES = 0.750), AJ (height: ES = 0.537, peak power: ES = 0.441), 1RM-SS (ES = 0.671) compared to the TCT group and the muscle thicknes at the mid of the quadriceps femoris (ES = 0.504) after FCTEO training. Since volleyball requires lower limb strength and explosive effort during repeated jumps and spiking, these results suggest that FCTEO affects muscular adaptation in a way that improves performance in well-trained female volleyball players.